A expansão urbana em áreas de fundo de vale na cidade de Bauru-SP - Barbosa, Valter Luís (2006)
Bauru is considered an important city in the regional context of the São Paulo State. It is situated in the center-west of the state and its main economical activity is the service sector. The urban growth of Bauru has occurred in the bottom of the valley and that compromised the ecological condition in the urban mean. Also known as the "city without limits", Bauru has been suffering with the public politics of the city government, associated with the conditions of the urban environment appropriations, the financial capital and real state, besides the irregular use of the urban soil, all this contributing to accentuate the unbalance of the physical nature, the landscape and the social conditions of the inhabitants that live in areas situated in the bottom of the valley. The purpose of this research is to identify and to analyse the importance of the Special Sectors of Conservation of the Bottom of the Valley also called SEC in the urban system and in the maintenance of life quality to local communities. In this investigation, we used and analysed the laws established by the Town's Plan, in order to check the execution of the environment legislation about the occupation of urban space in the areas of the bottom of the valley. It was observed that the social environment degradation in the Special Sectors of Conservation of the Bottom of the Valley SEC in Bauru has became evident, this meaning that the urban environment is in crisis and it is risky for the ecosystem capacity. It was also verified that the growth of the city has been orientated to the appropriation of the urban space, without considering the social and the natural aspects of the environment, resulting in fragmented actions and in the wasteful of public resources. The public practices of Bauru local administration does not accomplish the legislation in effect by the Town's Plan, risking the proper development of the city when avoiding the environment problem in the Special Sectors of Conservation in the Bottom of the Valley. The urban expansion growth to new areas made that the bottom of the valley could express how are the relations between the public power and the different kinds of interests established in the urban environment, making the Special Sectors of Bottom of the Valley objects to be used to a few people, in detriment of the most of the population, that live in helpless situation, contributing to accelerate the degradation of the social-environment process. This work has the intention to be helpful for the comprehension of the physical nature relations in Bauru urban environment and to add support as to make it easier to the local government to direct its actions to a democratic administration concerning to the city urban expansion.